Circulating let-7 Levels in Serum Correlate With the Severity of Hepatic Fibrosis in Chronic Hepatitis C. (22nd October 2018) - Matsuura, Kentaro; Aizawa, Nobuhiro; Enomoto, Hirayuki; Nishiguchi, Shuhei; Toyoda, Hidenori; Kumada, Takashi; Iio, Etsuko; Ito, Kyoko; Ogawa, Shintaro; Isogawa, Masanori; Alter, Harvey J; Tanaka, Yasuhito
Abstract: Background: Evaluating the progression of hepatic fibrosis in chronic hepatitis C (CHC) is critical, and identifying a predictive biomarker for fibrosis will be helpful for implementing personalized surveillance of hepatocellular carcinoma after the elimination of hepatitis C virus by antiviral therapy. This study aimed to investigate the association of circulating let-7a-5p levels with severity of hepatic fibrosis. Methods: We analyzed circulating let-7a-5p levels in serum and serum-derived extracellular vesicles (EVs) in 84 Japanese CHC patients who underwent a liver biopsy by quantitative real-time polymerase chain reaction, and investigated the association of its levels with histological hepatic fibrotic stage, liver stiffness, and several hepatic fibrotic markers. Results: The levels of let-7a-5p in serum and EVs were significantly lower in patients with liver cirrhosis. Additionally, the serum let-7a-5p level correlated significantly with hepatic fibrotic markers, Mac-2 binding protein glycan isomer (M2BPGi), fibrosis-4 (FIB-4) index, aspartate aminotransferase-to-platelet ratio index (APRI), and liver stiffness, evaluated by transient elastography. Furthermore, the serum let-7a-5p level was superior to M2BPGi, FIB-4, and APRI and was comparable to liver stiffness in discriminating liver cirrhosis. Conclusions: These results provide evidence that circulating let-7a-5p in serum may serve as a surrogate marker for severity of hepatic fibrosis in CHC.